THE IMPORTANCE OF LINGUA POETICS ON LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Due to the fact that artistic texts often reveal the possibilities of the figurativeness and expressiveness of our language, it is important to study the participation of linguistic means in these texts in stylistic and linguopoetic aspects. Therefore, in Karakalpak linguistics, a number of works have been created. The article provides the importance of linguapoetics on linguistics.